In Defense of Pharmaceutically Enhancing Human Morality - Evangelos D. Protopapadakis, PhD (Elsevier, 2017)
Purpose: I will discuss the prospect of pharmaceutically enhancing human morality and decision making in such a way as to eliminate morally unjustifiable choices and promote desirable ones. Background: Our species in the relatively short period since it has emerged has enormously advanced in knowledge, science, and technical progress. When it comes to moral development, the distance it has covered is almost negligible. What if we could medically accelerate our moral development? What if we could once and for all render our species totally immune to certain vices? Methodology: I will examine whether pharmaceutically intervening in human morality would compromise the autonomy of moral agents. I will argue that the argument from the autonomy of the moral agent is neither stable nor convincing. Conclusions: In the light of Kantian ethics we might consider moral enhancement by pharmaceutical means to be a perfect duty for moral agents.